Transformative changes towards carbon neutral society: Barriers and drivers - Dalia Štreimikienė (Contemporary Economics, 2023)
The barriers of climate change mitigation and mechanisms to overcome these barriers and achieve transformative changes towards carbon neutral society need to be investigated in order to define the main drivers and barriers of transformative change towards carbon neutrality and how policies and measures can be developed to overcome barriers and to support drivers. The main drivers of transformative change that include various types of institutions including social norms and rules, governance schemes, cultural values, demographic, social, economic, technical and technological elements are analysed and systematized based on literature review. Transformative change towards carbon neutral society necessitates systematic changes as simple scaling-up is not enough. These important roles are the levers or main pathways for achieving transformative change towards a carbon neutral society.
Keywords: H30; P18; Q20; Q30; 330; transformative changes; carbon neutral society; barriers; drivers; policies and measures